The export-diversifying impact of Japanese and US foreign direct investments in the Indian manufacturing sector - Banga, Rashmi (Journal of International Business Studies, 2006)
The paper highlights the export-diversifying impact of foreign direct investment (FDI) in a developing country. FDI may lead to export diversification in the host country if it positively affects the export intensity of industries that have a low share in world exports. Indirectly, FDI may encourage export diversification through spillover effects: that is, the presence of FDI in an industry may increase the export intensity of domestic firms. The empirical results for the Indian economy in the post-liberalisation period show that FDI from the US has led to diversification of India's exports, both directly and indirectly. However, Japanese FDI has had no significant impact on India's exports.